Generation of Functional Human Cardiac Progenitor Cells by High-Efficiency Protein Transduction. (12th November 2015) - Li, Xiao-Hong; Li, Qianqian; Jiang, Lin; Deng, Chunyu; Liu, Zaiyi; Fu, Yongheng; Zhang, Mengzhen; Tan, Honghong; Feng, Yuliang; Shan, Zhixin; Wang, Jianjun; Yu, Xi-Yong
Abstract : Protein-induced cardiac progenitor cells (CPCs) that are directly reprogrammed in vitro might be applicable for replacing dead heart muscle after myocardial infarction. The use of undifferentiated CPCs as building blocks to grow specific tissue types in vivo is of great interest for regenerating the myocardium. Abstract: : The reprogramming of fibroblasts to induced pluripotent stem cells raises the possibility that somatic cells could be directly reprogrammed to cardiac progenitor cells (CPCs). The present study aimed to assess highly efficient protein-based approaches to reduce or eliminate the genetic manipulations to generate CPCs for cardiac regeneration therapy. A combination of QQ-reagent-modified Gata4, Hand2, Mef2c, and Tbx5 and three cytokines rapidly and efficiently reprogrammed human dermal fibroblasts (HDFs) into CPCs. This reprogramming process enriched trimethylated histone H3 lysine 4, monoacetylated histone H3 lysine 9, and Baf60c at the Nkx2.5 cardiac enhancer region by the chromatin immunoprecipitation quantitative polymerase chain reaction assay. Protein-induced CPCs transplanted into rat hearts after myocardial infarction improved cardiac function, and this was related to differentiation into cardiomyocyte-like cells. These findings demonstrate that the highly efficient protein-transduction method can directly reprogram HDFs into CPCs. This protein reprogramming strategy lays the foundation for future refinements both in vitro and in vivo and might provide a source of CPCs for regenerative approaches. Significance: The findings from the present study have demonstrated an efficient protein-transduction method of directly reprogramming fibroblasts into cardiac progenitor cells. These results have great potential in cell-based therapy for cardiovascular diseases.